Kako nagovoriti in kaj spodbuditi - Žagar, Janja (Etnolog. Nova vrsta (Ljubljana), 2010)
The article addresses the basic idea of the multi-part concept of the SEM's permanent exhibition. It describes the conceptual principles of the second permanent exhibition entitled I, We and Others: Images of my World. The exhibition is dedicated to man and his searching of his own place in the world. It does not highlight Slovene culture or Slovene cultural heritage, but rather draws attention to the relative nature of the concept of Us and ours, and to the meaning of Other and otherness. The article focuses on the ideas and reservations that guided the selection of material and ways of usingit, because they have a key impact on the final interpretation. It explains the strategies of communicating with the visitors and the goals we set for the exhibition.
Keywords: ocene in poročila; stalne razstave; Slovenski etnografski muzej; Ljubljana; ethnology; etnologija; Slovenia; Slovenija